Sounds of Freedom: Songs in the 1960s Southern Civil Rights Movement - Stefani, Anne (Complutense Journal of English Studies, 2015)
Songs are part of a long tradition of dissent and struggle in American culture since the seventeenth century. In the twentieth century, this tradition is well illustrated by the Freedom Songs of the 1960s civil rights movement, a distinctive feature of the struggle for black freedom in the South. Freedom songs were used within and outside the movement to sustain as well as to publicize the struggle. The present article analyzes the nature and function of those songs, demonstrating that they represented much more than protest songs. It shows that beyond their most obvious function, which was to mobilize and cement collective participation in the various demonstrations and actions of nonviolent resistance to segregation, Freedom Songs had a transforming power over individuals. In the context of the southern Freedom Movement, singing became an existential experience, a second birth through which African Americans re-appropriated their culture and constructed a new identity for themselves and for their people. Freedom songs thus can be said to have contributed not only to defeating white supremacy in the South but also to empowering African Americans by reconnecting them to their culture and by providing each individual the way to achieve his or her inner liberation.